Capital regulation induced reaching for systematic yield: Financial instability through fire sales - Boermans, Martijn A.; van der Kroft, Bram (Journal of Banking & Finance, 2024)
Credit rating-based capital regulation induces financial institutions to take on additional systematic risk. In this paper, we uncover interconnected channels through which this systematic risk hoarding affects financial stability using a proprietary ECB bond holdings dataset. First, banks and insurance corporations effectively reduce their capital buffers by hoarding bonds with high systematic credit risk. Second, this hoarding increases the portfolio concentration of credit rating-constrained and unconstrained financial institutions. Third, in addition to the general tendency of regulated financial institutions to fire sale bonds after rating downgrades, we reveal even larger fire sales precisely when their regulatory advantages of reaching for systematic yield disappear. Using a shock in capital regulation, we establish this causal relationship between the severity of fire sales and the tendencies of regulatory-constrained financial institutions to seek bonds with high systematic credit risk. Such systematic risk hoarding reduces capital buffer by an additional 16% in economic downturns.